Impact Dynamic Behavior and Deformation Mode of a Lightweight-Coated Honeycomb Steel Structure - Luo, Ning; Yuan, Yishuo; Fan, Xueru; Suo, Yunchen; Mou, Gongyu (Frontiers in Materials, 2022)
Honeycomb materials have attracted people’s attention because of their light weight, high specific strength, high specific stiffness, and excellent impact resistance and energy absorption. At present, the specific materials have been widely used in aerospace, transportation, mechanical construction, energy, and chemical industry. The mechanical properties of honeycomb steel with special coating under quasi-static and dynamic compression were studied by using the universal strength testing machine (TAWD-2000) and split Hopkinson pressure bar (SHPB) devices. The results showed that the stress–strain curves obtained from the quasi-static compression experiment showed the characteristics of three typical deformation stages of porous materials: the elastic deformation stage, stress platform stage, and densification stage. Due to the fact that the loading time of the dynamic compression experiment is very short and because of the effect of the sample’s height, there was no densification stage in the stress–strain curves under dynamic loading. The dynamic compression deformation process of the samples was captured by the high-speed photography equipment, and its different deformations and failure modes were analyzed in combination with the characteristics of stress–strain curves. The increasing relationship between the peak stress and strain rate showed the strain rate sensitivity of the honeycomb structure. The dynamic energy absorption characteristics of honeycomb materials were described and analyzed by using the dynamic energy absorption capacity and dynamic energy absorption efficiency. By using finite element simulation software, the same structure of the honeycomb steel was modeled and analyzed to explore the causes of dynamic compression failure. Because of its special mechanical properties and failure modes, this honeycomb structure material will have a broader research and application prospect in the future.